7+10s+-1s+1s=

Simple and best practice solution for 7+10s+-1s+1s= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+10s+-1s+1s= equation:


Simplifying
7 + 10s + -1s + 1s = 0

Combine like terms: 10s + -1s = 9s
7 + 9s + 1s = 0

Combine like terms: 9s + 1s = 10s
7 + 10s = 0

Solving
7 + 10s = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 10s = 0 + -7

Combine like terms: 7 + -7 = 0
0 + 10s = 0 + -7
10s = 0 + -7

Combine like terms: 0 + -7 = -7
10s = -7

Divide each side by '10'.
s = -0.7

Simplifying
s = -0.7

See similar equations:

| -82-5x=3x+54 | | 7+7t-4+-6= | | -48-5x=12-7x | | 10-4yi=2x+24i | | 2(-2+x)=x-.875 | | 72/10,000 | | 10(10+c)+2=10 | | 10(10+c)+2=100 | | -14+12x=12+10x | | -5u+14=4u+32 | | 1.5d+3.25=1+2.25s | | 100(10+c)+0=10 | | xsquared-9x=-8 | | 1/3m=33 | | -3u+15=9u-45 | | 6x-30=x+16 | | -83-2x=-10x+93 | | x-1=-2/4x-1/4 | | 4X+17+28=6X | | 5/9=b-1/3 | | 1+5p=11+3p | | -56+3x=5x+80 | | 4(7y-6)-(9y+9)= | | 8(12+9)= | | 6m+2=8 | | a+(-11)=-13 | | 7x+10=210 | | 1+6k+8=-6k+9 | | 6(y-5)-4=20 | | -5x-17=-x-1 | | -8y^2+-5y^2+7y^2+-7y^2= | | (5^-2)x^-1/x^4(y^2) |

Equations solver categories